SUSTAINABLE QUALITY – A CHALLENGE FOR GAINING NEW KNOWLEDGE FOR ACHIEVING A CLIMATE-RESILIENT FUTURE IN THE COMING YEARS - Velkoska, Cvetanka (International Scientific Journal Vision, 2021)
This paper presents the identified conditions, strategies and public policies expected to stimulate the development of scientific and practical findings with a view of improving the global eco-system by smartly shifting towards long-lasting solutions and success, through integrated and joint efforts by researchers, practitioners, decision-makers, regulatory bodies, and civil societies. With the growth of knowledge-based society, we should strengthen our climate capabilities, institutions, knowledge, skills, and learning about all facets of the sustainability, with a view of providing a climate-resilient future. The need of sustainable products viewed through the environmental, economic, and social prism, should stimulate the development of new values, attitudes, and behavior in society which will proactively mitigate and eliminate the consequences arising from pollution and global warming, ozone depletion, energy intensity, toxicity, etc. It is inevitable to devise a road map of actions along the science-policy-society axis, as well as new metrics to overcome the momentum coming in the following decades, especially because of the pressure of the intensive digitalization on the demand and the exploitation of rare metals which will open the topics of technical and technological procedures for their recycling and disposal. The science of sustainability must strengthen.